PREDIKSI FINANCIAL DISTRESS MENGGUNAKAN VARIABEL KEUANGAN DAN VARIABEL NON KEUANGAN - Dinda Permata; Agung Juliarto (Diponegoro Journal of Accounting, 2021)
This study aims to predict the incidence of financial distress in a company using financial and non-financial variables. Financial variables in this tudy using the indicators Interest Coverage Ratio (ICR), Operating Cash Flow per Sahres (OCFS), and Long Term Debt Equity (LTDER). And non financial variabels in this study using the indicators age of company and Promotor Holding (PH)The population in this study are all of the companies listed on the Indonesia Stock Exchange and contiously published financial statement in the year 2016-2019. Based on purposive sampling method, sampples obtained are 62 companies in the period 2016-2019, so obtain 248 observations. As for the criteria of financial distress in this study was measured by using operating profit, basic earning per shares, and devides per shares, whilst statistic analysis that used in this study was logistic regression.Results show that the Interest Coverage Ratio (ICR), Long term Debt Equity are financial variables that have significant influence on predicting financial distress in a company, whereas Operating Cash Flow Per Shares (OCFS) has no a significant effect on predicting financial distress in a company. As for non-financial variables, age of company and Promoter Holding (PH), are statistically proven in predicting company financial distress.